Creating Transformative Leaders of Social Justice in Education. (2nd January 2023) - Makaiau, Amber S.; Halagao, Patricia E.; Thao, Ger
Abstract : Three colleagues critically reflect on their experiences as educators, curriculum designers, leaders, and activists who set out to apply social justice education and transformative leadership scholarship to the creation of a Leaders of Social Justice in Education course. They begin with their background, the diverse change agents selected to build a movement of leaders, and the educational context. Second, a theoretical framework is presented to explain the overall goals of the project and the development of the course. Third, the course curriculum and website created during the COVID-19 pandemic is described, specifically the culminating Social Justice Action Project. Fourth, outcomes of the project are identified, including lessons learned about transformative leadership in the context of social justice education. At the paper's conclusion, the authors reflect on the course and explain why ongoing learning opportunities, structures, and collaboratives are needed for cultivating and nurturing the next generation of leaders in social justice education.